Sex Cord Stromal Tumors in Children and Adolescents: A First Report by The South African Children's Cancer Study Group (1990-2015). Issue 5 (July 2021) - Hendricks, Marc; Cois, Annibale; Geel, Jennifer; van Heerden, Jaques; Naidu, Gita; du Plessis, Jan; Bassingthwaighte, Mairi; van Zyl, Anel; Uys, Ronelle; Bϋchner, Ane; Rowe, Biance; Omar, Fareed; et al.
Abstract : Objectives: Pediatric sex cord stromal tumors (SCSTs) are extremely rare and there are no reported data from Africa. The authors evaluated the outcomes of children and adolescents with biopsy-proven SCSTs in preparation for the introduction of a national protocol. Materials and Methods: Retrospective data were collated from 9 South African pediatric oncology units from January 1990 to December 2015. Kaplan-Meier analysis was performed to estimate overall survival (OS) and event-free survival. Results: Twenty-three patients were diagnosed with SCSTs, 3 male and 20 female individuals, during the study period. Histologies included 1 thecoma, 9 Sertoli-Leydig cell tumors, and 13 juvenile granulosa cell tumors. Stage I tumors predominated (n=14; 60.9%), with 2 stage II (8.7%), 5 stage III (21.7%), and 2 stage IV tumors (8.7%). The upfront resection rate was 91.3% with no reported surgical morbidity or mortality and an OS of 82.1%. Chemotherapy approaches were not standardized. Most children (81.8%), except 2, had recognized platinum-based regimens. Chemotherapy-related toxicity was minimal and acceptable. Assessment of glomerular filtration rate and audiology assessments were infrequent and not standardized. Three patients were lost to follow-up. Conclusions: Although the numbers in this cohort are small, this study represents the first national cohort in Africa. The 5-year OS of 82.1% was encouraging. Standardized management of rare tumors like SCSTs is critical to improve ensure OS and address potential long-term sequelae.